2012
DOI: 10.1371/journal.pone.0049478
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus Factor Modulation of Effects of Smoking and Age on Psychomotor Performance, Intelligence, Personality Profile, and Health in Czech Soldiers

Abstract: BackgroundRhesus-positive and rhesus-negative persons differ in the presence-absence of highly immunogenic RhD protein on the erythrocyte membrane. This protein is a component of NH3 or CO2 pump whose physiological role is unknown. Several recent studies have shown that RhD positivity protects against effects of latent toxoplasmosis on motor performance and personality. It is not known, however, whether the RhD phenotype modifies exclusively the response of the body to toxoplasmosis or whether it also influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

6
3

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 40 publications
4
27
0
Order By: Relevance
“…The fourth study has reported opposite relation of toxoplasmosis with Cattell's ego strength, praxernia, and ergic tension and Cloninger's cooperativeness in RhD-positive and RhD-negative blood donors [29]. The latter study also indicates that RhD phenotype might play an important role not only in the toxoplasmosis-associated differences but also in the age-associated differences in specific personality traits.. Another recent study shows that RhD phenotype could also play a role in correlations of age and smoking with psychomotor performance, intelligence and health of draftees [47]. The results of the current study are in an agreement with the already published data.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The fourth study has reported opposite relation of toxoplasmosis with Cattell's ego strength, praxernia, and ergic tension and Cloninger's cooperativeness in RhD-positive and RhD-negative blood donors [29]. The latter study also indicates that RhD phenotype might play an important role not only in the toxoplasmosis-associated differences but also in the age-associated differences in specific personality traits.. Another recent study shows that RhD phenotype could also play a role in correlations of age and smoking with psychomotor performance, intelligence and health of draftees [47]. The results of the current study are in an agreement with the already published data.…”
Section: Discussionmentioning
confidence: 75%
“…It must be reminded, however, that the ABO blood group system rather than the Rhesus factor system was nearly always examined in these studies, see [61]–[64]. Our results imply that in future behavioural studies the attention should be focused not only on the ABO system but also on RhD phenotype and that important confounding variables, especially Toxoplasma infection and smoking [47] should be controlled.…”
Section: Discussionmentioning
confidence: 89%
“…While the prevalence of RhD-negative subjects in Caucasian populations is about 16%, it is much lower in the population of people of Asian and African origin (Mourant 1954). It must be admitted, however, that RhD-negative individuals are subject to stronger negative effects of aging and smoking on health estimated on the basis of the self-rated number of common viral and bacterial diseases in the past year, regardless of Toxoplasma infection status, and that RhD positivity probably protects against a broader spectrum of negative factors than just the Toxoplasma infection (Flegr et al 2010(Flegr et al , 2012. A possible physiological mechanism of physiological and behavioural effects of RhD phenotype that was based on RhD negativity-associated anoxia in certain parts of nervous system was suggested by Prandota (2012).…”
Section: Discussionmentioning
confidence: 99%
“…Rh positive and Rh negative subjects express different sensitivity to the effects of latent toxoplasmosis on psychomotor performance (Flegr et al, 2008c(Flegr et al, , 2012aNovotná et al, 2008) cognitive performance (Flegr et al, 2012a(Flegr et al, , 2013, personality profile (Cattell, 1972;Flegr et al, 2010Flegr et al, , 2012aFlegr et al, , 2013, and mental health (Holub et al, 2011) and also differ in their health status and the incidence of certain disorders Flegr, 2016), but see (Halmin et al, 2017). Many effects of toxoplasmosis are much stronger in Rh negative subjects and some can be detected only in them (Flegr et al, 2009;Kaňková et al, 2010).…”
Section: Introductionmentioning
confidence: 99%